Analisis Pengaruh Religiusitas, Literasi Halal, dan Sikap Konsumtif Terhadap Preferensi Wisatawan pada Pariwisata Halal di Solok - Andika Putra; Nurizal Ismail; Solahuddin Al-Ayubi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this study is to evaluate the impact of three main factors: Religiousness, Halal Literacy, and Consumer Attitude on halal tourism preferences in Solok. The method employed in this research is Partial Least Square Structural Equation Modeling (SEM-PLS). The study involved 150 participants from various segments of society. The analysis results indicate that Halal Literacy significantly and positively contributes to consumer preferences in choosing halal tourism destinations. Conversely, Religiousness shows a negative influence on tourist preferences, suggesting that religious understanding does not always play a primary role in tourism decision-making. On the other hand, Consumer Attitude exhibits a significant positive impact on tourist preferences in Solok. These findings have significant implications for the halal tourism industry in Solok, highlighting the importance of halal literacy awareness and consumer attitudes towards halal products in enhancing the attractiveness of tourism destinations.